Cerebral Air Embolism from Angioinvasive Cavitary Aspergillosis - Chen Lin; George A. Barrio; Lynne M. Hurwitz; Peter G. Kranz (Case Reports in Neurological Medicine)
Background. Nontraumatic cerebral air embolism cases are rare. We report a case of an air embolism resulting in cerebral infarction related to angioinvasive cavitary aspergillosis. To our knowledge, there have been no previous reports associating these two conditions together. Case Presentation. A 32-year-old female was admitted for treatment of acute lymphoblastic leukemia (ALL). Her hospital course was complicated by pulmonary aspergillosis. On hospital day 55, she acutely developed severe global aphasia with right hemiplegia. A CT and CT-angiogram of her head and neck were obtained demonstrating intravascular air emboli within the left middle cerebral artery (MCA) branches. She was emergently taken for hyperbaric oxygen therapy (HBOT). Evaluation for origin of the air embolus revealed an air focus along the left lower pulmonary vein. Over the course of 48 hours, her symptoms significantly improved. Conclusion. This unique case details an immunocompromised patient with pulmonary aspergillosis cavitary lesions that invaded into a pulmonary vein and caused a cerebral air embolism. With cerebral air embolisms, the acute treatment option differs from the typical ischemic stroke pathway and the provider should consider emergent HBOT. This case highlights the importance of considering atypical causes of acute ischemic stroke.